2020
DOI: 10.1002/aenm.202003367
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Thermally Stable, and Mechanically Robust All‐Polymer Solar Cells Consisting of the Same Benzodithiophene Unit‐Based Polymer Acceptor and Donor with High Molecular Compatibility

Abstract: All‐polymer solar cells (all‐PSCs) are a highly attractive class of photovoltaics for wearable and portable electronics due to their excellent morphological and mechanical stabilities. Recently, new types of polymer acceptors (PAs) consisting of non‐fullerene small molecule acceptors (NFSMAs) with strong light absorption have been proposed to enhance the power conversion efficiency (PCE) of all‐PSCs. However, polymerization of NFSMAs often reduces entropy of mixing in PSC blends and prevents the formation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 71 publications
(47 reference statements)
0
92
0
Order By: Relevance
“…This notable enhancement in the mechanical ductility of the blends was attributed to tie molecules and chain entanglements formulated by the long chains of high-MW P A , dramatically improving the dissipation of external stress. 10 , 68 Based on the aforementioned results and the photovoltaic parameters presented in Figure 2 and Table 2 , the PSC incorporating 20 wt % of the P A demonstrates optimal photovoltaic performance (PCE exceeding 15%) and mechanical robustness (COS exceeding 10%). The PCEs and COS values (obtained by the pseudo-free-standing tensile test) of the PSCs developed in this study were compared with those of previously reported PSCs ( Figure 4 d and Table S6 ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…This notable enhancement in the mechanical ductility of the blends was attributed to tie molecules and chain entanglements formulated by the long chains of high-MW P A , dramatically improving the dissipation of external stress. 10 , 68 Based on the aforementioned results and the photovoltaic parameters presented in Figure 2 and Table 2 , the PSC incorporating 20 wt % of the P A demonstrates optimal photovoltaic performance (PCE exceeding 15%) and mechanical robustness (COS exceeding 10%). The PCEs and COS values (obtained by the pseudo-free-standing tensile test) of the PSCs developed in this study were compared with those of previously reported PSCs ( Figure 4 d and Table S6 ).…”
Section: Resultsmentioning
confidence: 92%
“…This brittleness of the Y7 thin film was attributed to its highly rigid ladder-type backbone structure, which is consistent with the reported characteristic brittleness of SMA materials. 10 , 12 In stark contrast, the P(NDI2OD-T2) P A had high ductility with a COS and toughness of 39.20% and 12.0 MJ m –3 , respectively. The superior ductility of P(NDI2OD-T2) was attributed to its high MW ( M w = 267 kg mol –1 ) exceeding its critical MW, which affords the formation of tie molecules and entangled chains in the thin film.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…16,18,19 Additionally, due to interchain entanglement between the polymer donor ( P D ) and the polymer acceptor ( P A ), the P A s are normally perceived to possess some unique stability properties like superior resilience against thermal and mechanical stress, as compared to the relevant fullerene and NFA materials. 10,20,21 Despite this, performance attenuation and morphological evolution in the relevant all-PSCs are still observed under increased thermal heating or even exposure to the ambient conditions. 22,23 In particular, appropriate investigations have initially shown that the material structure-determined stability was also present in the all-polymer systems.…”
Section: Introductionmentioning
confidence: 99%